The Composition of Human Capital and Economic Growth: Evidence from Aceh and West Papua Provinces, Indonesia - Zata Hasyyati; Sahara Sahara (International Journal of Economics and Financial Issues, 2020)
This paper investigates the importance of human capital and each educational level on economic growth in Aceh and West Papua from 2010 to 2017. Examining the dynamic panel data using difference generalized method of moments shows there is insignificant impact of tertiary education on economic growth. Both provinces have U-shape effect of human capital composition, which indicates primary and secondary education seems to contribute more on the economy. Hence, the government should solve these educational levels first. Since the data showed the indication of low quality of educators, teachers' skills improvement on teaching and their wellbeing should be prioritized.